Selected aspects of health among the children of homes for street children and their hope for the future. - Tanaz, W. V.L (My University, 2003)
This study was a cross sectional descriptive study and consisted of three parts. Socio demographic and some health information were collected during the first part using an interviewer administered semi structured questionnaire. Second part of the study was a clinical examination conducted to ascertain their health problems. A clinical examination form was used during this part of the study. Third part of the study was done to assess their emergence of hope qualitatively, by conducting focus group discussions. First part of the study revealed that the mean age of children was 10 years. Majority of the children were female. When the ethnicity was considered the majority was Sinhalese. Percentages of Tamils and Muslims were relatively higher than the national figures for which the underlying factors were not revealed. A most all of them were currently attending school but the majority (34 percentage) were not in the age appropriate class in the school. Their literacy level was relatively lower than the national figure. 32 percentage of them were engaging in income generating activities. During the second part of the study it was revealed that the perceived general health status was good for the majority of them. Skin problems and oral health problems were common among them. Scabies was common. Main oral health problems identified were carries teeth and gingivitis. There were visible signs of emerging hope among them, which was at a lower level according to the analysis. The children were found to be still suffering from the implications of the difficult times that they have under gone under during the past. Therefore in conclusion the educational level was low and the literacy level was relatively lower than the national adult literacy rate. And there were some preventable health problems among them. Hence it is recommended to : Pay more attention to improve their educational level, Literacy level and their employability; Have comprehensive health educational program for the children as well as to the caretakers in the homes; Implement community and family based interventions to empower the children; Have programs to support them to overcome their mental trauma due to the past difficult times that they have under gone.